Ichneumonid wasps from Madagascar. V. Ichneumonidae Cremastinae - Rousse, Pascal; Villemant, Claire; Seyrig, Andre (Zootaxa, 2011)
Four species of Cremastinae (Hymenoptera: Ichneumonidae) species were previously known from Madagascar. The subfamily Cremastinae occurring in Madagascar is revised, it includes 21 species in seven genera (Cremastus Gravenhorst, 1829, Eurygenys Townes, 1971, Fafana gen. nov., Pimplomorpha Cameron, 1906, Pristomerus Curtis, 1836, Temelucha Förster, 1869 and Trathala Cameron, 1899). One new genus (Fafana gen. nov.), and 12 new species are described (Eury- genys bilbo sp. nov., E. gamour sp. nov., E. kerlioretensis sp. nov., Fafana timhoti sp. nov., Pimplomorpha mahafaty sp. nov., P. quilicii sp. nov., Temelucha talibarti sp. nov., T. teloloko sp. nov., Trathala agnielae sp. nov., T. lachaisae sp. nov., T. mimouna sp. nov. and T. orchestotrichias sp. nov.). The nine remaining species are redescribed. A key to all genera and species in Madagascar is provided.